Extraordinary kinetic inertness of lanthanide(iii) complexes of pyridine-rigidified 18-membered hexaazamacrocycles with four acetate pendant arms - Faltejsek, Jan; Urbanovský, Peter; Kubíček, Vojtěch; Havlíčková, Jana; Císařová, Ivana; Kotek, Jan; Hermann, Petr (Chemical science, 2025)
Large polyazamacrocycles are used for the complexation of large metal ions. However, their coordination chemistry has not been frequently studied until now. An eighteen-membered macrocycle with two rigidifying pyridine rings and four aliphatic amino groups substituted with four acetic acid pendants, H4pyta, provides a large ligand cavity and coordination number (CN) up to 10. Trivalent lanthanides were chosen to study the effect of metal ion size on the properties of H4pyta complexes. The complexes were formed under relatively mild conditions and two isomers were observed, depending on the Ln(iii) ion, in different mutual ratios during the synthesis. Going to smaller Ln(iii) ions, the CN decreases from 10 to 9. Stability constants of Ln(iii)-H4pyta complexes with CN 10 are comparable with those of Ln(iii)-H4dota complexes despite the lower overall basicity of H4pyta. In the ten-coordinated isomers, Ln(iii) ions are perfectly 3D-wrapped inside the ligand cavity, and the ligand is minimally distorted. It leads to extreme kinetic inertness of the complexes. Dissociation of the Ln(iii)-H4pyta complexes in 5 M HClO4 and at 90 °C is very slow and requires up to several hours; the inertness is 102-104 times higher than that of the Ln(iii)-H4dota complexes. The solid-state structures point to the symmetric wrapping of metal ions and CN 10 being responsible for the stability of species multiply protonated on the coordinated acetate groups. The results suggest that H4pyta can be considered a leading scaffold for the future development of ligands intended for large metal ion binding in nuclear medicine, e.g. for α-emitting radioisotopes from the bottom of the periodic table.